Efficacy and Safety of Direct Oral Anticoagulants in Patients With Atrial Fibrillation and High Thromboembolic Risk. A Systematic Review - Acanfora, Domenico; Ciccone, Marco Matteo; Scicchitano, Pietro; Ricci, Giovanni; Acanfora, Chiara; Uguccioni, Massimo; Casucci, Gerardo (Frontiers in Pharmacology, 2019)
Background. The aim of the study was to evaluate the efficacy and safety of direct oral anticoagulants (DOACs) in a subgroup of patients with atrial fibrillation (AF), CHADS2 score≥3, advanced age, and heart failure (HF) coming from the main DOACs randomized clinical trials. Methods. We searched MEDLINE, MEDLINE In-Process, and Other Non-Indexed Citations. EMBASE, PubMed, and the Cochrane Central Register of Controlled Trials. English-language articles published from 2002 to March 2019 dealing with DOACs for preventing thrombotic events in AF were considered. We did not conduct any statistical analyses as indirect comparison between DOACs represents hypothesis generators. Results. This systematic review was restricted to the subgroup of patients with CHADS2 score≥3 (n=31,203), elderly (n=24,788), and with HF (n=29,297) derived from the pivotal trials. Risk index (RI) was calculated. The RI for stroke/systemic embolism was similar in all of the patients treated with DOACs or warfarin. The lowest RI was in rivaroxaban patients (CHADS2 score≥3: RI=0.04; elderly: RI=0.09; HF: RI=0.05). The RIs for bleeding were higher in patients treated with dabigatran (CHADS2 score≥3: RI110=0.23; elderly: RI110=0.22; HF: RI110=0.16. CHADS2 score≥3: RI150=0.30; elderly: RI150=0.24; HF: RI150=0.16). The bleeding RIs were higher with apixaban (CHADS2 score≥3: RI=0.23; elderly: RI=0.25; HF: RI=0.14) and dabigatran (CHADS2score≥3: RI=0.28; elderly: RI=0.21; HF: RI=0.19). Conclusions. The use of DOACs is a reasonable alternative to vitamin-K antagonists in AF patients with CHADS2 score≥3, advanced age, and HF. The RI constitutes a useful, additional tool to facilitate clinicians in choosing DOACs or Warfarin in particular category of AF patients.